1997
DOI: 10.1002/(sici)1098-2299(199701)40:1<68::aid-ddr7>3.3.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Effects of repeated treatments with an extract of Ginkgo biloba (EGb 761) and bilobalide on liver and muscle glycogen contents in the non‐insulin‐dependent diabetic rat

Abstract: The effects of repeated (15-day) oral treatments with an extract of Ginkgo biloba (EGb 761; 50 mg/kg/day) or with its terpenoid constituent, bilobalide (2 mg/kg/day), were assessed in normal rats and in rats that had been previously injected with streptozotocin (50 mg/kg, i.p. in saline solution), a dose which provided a model of non-insulin-dependent diabetes mellitus (NIDDM). In this model of diabetes, blood glucose is significantly increased while the circulating insulin level remains unchanged. Glucose pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Considering these situations and the efficacy of GBE reported so far (Iliff and Auer, 1983;Lanthony and Cosson, 1988;Doly et al, 1992;Rapin et al, 1997), the simultaneous intake of GBE and anti-diabetic drug is most likely to occur in the elderly. For the safe use of both GBE and drugs, it is important to elucidate how GBE taken as a dietary supplement modifies the efficacy of therapeutic drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering these situations and the efficacy of GBE reported so far (Iliff and Auer, 1983;Lanthony and Cosson, 1988;Doly et al, 1992;Rapin et al, 1997), the simultaneous intake of GBE and anti-diabetic drug is most likely to occur in the elderly. For the safe use of both GBE and drugs, it is important to elucidate how GBE taken as a dietary supplement modifies the efficacy of therapeutic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, GBE has been shown to improve peripheral blood flow (Iliff and Auer, 1983) and is expected to prevent periphery necrosis and retinopathy in severe diabetes (Lanthony and Cosson, 1988;Doly et al, 1992). It is also reported that GBE inhibits the increment of blood glucose concentration in glucose-loaded diabetic rats (Rapin et al, 1997). Thus, the simultaneous intake of GBE and anti-diabetic agents might occur, particularly in elderly people.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports showed that Ginkgo extract reduced blood glucose (Rapin et al, 1997;Shankar et al, 2005;Tanaka et al, 2004). But, reduction mechanism of blood glucose was not consistent.…”
Section: Discussionmentioning
confidence: 98%
“…But, reduction mechanism of blood glucose was not consistent. Ginkgo extract lowered blood glucose via insulin-like action (Rapin et al, 1997), antioxidant activity (Shankar et al, 2005) or inhibitory effect of glucosidase (Tanaka et al, 2004). Especially, Kudolo reported that Ginkgo extract increased pancreatic beta-cell function in healthy subjects and in type 2 diabetic subjects with pancreatic exhaustion (Kudolo, 2000(Kudolo, , 2001 although the same treatment of Ginkgo extract produced no significant effect on beta-cell function in hyperinsulinemic type 2 diabetic subjects (Kudolo, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation